ANALISIS LAPORAN KEUANGAN INDUSTRI PENERBANGAN YANG TERDAFTAR DI BEI SEBELUM DAN SESUDAH COVID19 - Delfiani, Silvi; Ridhaningsih, Fitria; Febriyanti, Herlinda Fitri (Universitas Negeri Padang, 2023)
The aim of this study is to analyze the performance of companies in Indonesia that are listed on the Indonesian Stock Exchange in the period before and after the COVID-19 pandemic, or 2019 to 2022. An assessment of company performance is based on the ratio of liquidity, solvency, and profitability. The object of this research is a company that moves into the aviation industry and uses purposive sampling techniques. Thus, three airlines, GIAA, CMPP, and IATA, were obtained. From the results of this study, it is known that all the samples experienced a decrease in performance when the COVID-19 pandemic occurred, namely in 2020 and 2021. The COVID-19 pandemic has had a negative impact on company performance. Then in 2022, there was a fairly rapid improvement, led by the GIAA.